Homogeneous and heterogeneous gold catalysis for materials science - Hendrich, Christoph; Sekine, Kohei; Koshikawa, Takumi; Tanaka, Ken; Hashmi, A. Stephen K. (Chemical reviews, 2021)
Often stoichiometric amounts of gold find use in materials science; occasionally gold is even used as a support. This review discusses the contributions of gold catalysis, both homogeneous and heterogeneous, to the field of materials science. One topic is the synthesis of polymers, including nanowires and polyesters, the postcyclization of polymers, polymerization by cyclopropanation, and gold-catalyzed radical polymerization reactions. Other topics are dyes, phosphonium salts, and a wide range of extended conjugated π-systems, the latter ranging from acenes, pentalene derivatives, and different heterocyclic π-systems to fascinating applications in the synthesis of helical anellated aromatic molecules. The existing contributions clearly demonstrate the potential of gold catalysis for significant future impulses for the field of materials science.